Could futsal hold the key to developing the next generation of youth soccer players?. Issue 1 (2nd January 2018) - Yiannaki, Christopher; Carling, Christopher; Collins, Dave
ABSTRACT: The identification and development of talented players is a priority within elite soccer clubs and national governing bodies. Small-sided games training methods are commonly used in aiding player development. Yet the potential role for futsal (indoor 5 a-side equivalent to 11 a-side soccer) as part of contemporary youth player conditioning and skills acquisition training has received insufficient consideration. This absence might be linked to a lack of understanding due to a paucity of scientific evidence underpinning the potential role for futsal in aiding player development. While highlighting these issues, the present point-counterpoint article argues how futsal could impact positively on contemporary youth talent development processes.